Contar para vivir: La narrativa del estado de derecho en el Palacio de Justicia: análisis del informe de la comisión de la verdad de los hechos ocurridos en el Palacio de Justicia (2020)
The Palace of Justice has been one of the most painful moments in Colombia, as well as the era of the 80's. After 25 years, the Supreme Court of Justice of this country commissioned three judges: Jorge Aníbal Gómez Gallego, José Roberto Herrera Vergara and Nilson Pinilla Pinilla to form a Truth Commission that will render a report in which they will give an account of what occurred on November 6 and 7 of 1985 in Bogota, Colombia. Based on the theory presented by the Law and Literature movement -which emerged in the United States- is presented an analysis of the narrative found in the report presented by the Truth Commission of the events that occurred in the Palace of Justice. The narrative analysis carried out aims to (i) be a contribution to the academic discussion on the usefulness of other disciplines in legal analysis and (ii) account for an even larger project that was behind the Truth Commission: to strengthen the idea that the rule of law had to go on, stronger than ever. Restore faith in the law.